EFFECTS OF RESVERATROL AS AN ANTICANCER AGENT – A SYSTEMATIC REVIEW. - DR. TANU GARG; MAJOR (DR.) V. K. YADAV (International Journal of Pharma and Bio Sciences, 2014)
The objective of the review was to analyse the chemopreventive and chemotherapeutic effects of resveratrol in various types of cancers along with its possible mechanisms. Literature search in Pubmed, Ebsco and Google Scholar was done for articles on role of resveratrol in various types of carcinomas using the search terms resveratrol and cancer, anticancer agents. In vivo and in vitro human as well as animal studies were searched from year 2009 till date. We also searched the reference list of various articles for additional papers. Systematic analysis of these articles was done to look for the cancer preventive and protective actions of resveratrol and the mechanisms by which it exerts its anticancer effects. Resveratrol has shown significant chemotherapeutic and chemopreventive effects in various carcinomas by its antioxidant, anti-inflammatory effects and also interferes with initiation, promotion and progression stages of carcinogenesis in various cancer cells Resveratrol can be used as an adjuvant to other chemotherapeutic agents in various carcinomas. But it needs more clinical trials to establish its efficacy and safety as an anticancer agent in humans.